Helium and argon isotopic compositions of the Longquanzhan gold deposit in the Yishu fault zone and their geological implications - 胡华斌 孙爱群 牛树银 王宝德 李英平 (Acta geochimica, 2007)
The Longquanzhan gold deposit hosted in granitic cataclasites with mylontization of the foot wall of the main Yishui-Tangtou fault. ^3He/^He ratios in fluid inclusions range from 0. 14 to 0. 24 R/Ra, close to those of the crust-source helium. ^40Ar/^36Ar ratios were measured to be 289-1811, slightly higher than those of atmospheric argon. The results of analysis of helium and argon isotopes suggested that ore-forming fluids were derived chiefly from the crust. The δ^13O values of fluid inclusions from vein quartz range from -1.78‰ to 4.07‰, and the δD values of the fluid inclusions vary between -74‰ and -77‰. The hydrogen and oxygen isotope data indicated that the ore-forming fluid for the Longquanzhan gold deposit had mixed with meteoric water in the process of mineralization. This is consistent with the conclusion from the helium and argon isotope data.